Synthesis and Theoretical Investigation of 5-(4-Dimethylaminobenzylidene)thiobarbituric Acid - H. Mageed, Ahmed; A.S. Al-Ameed, Karrar (Asian Journal of Chemistry, 2013)
In this study, synthesis of 5-benzylidene thiobarbituric acid derivative has been described. The route of preparation involved the uses of thiobarbituric acid as starting material and treated with 4-dimethylaminobenzaldehyde compound to give required derivative. This compound was identified by spectroscopic methods; H NMR, FTIR and CHNS analysis and also by measuring its melting point. A theoretical investigation is performed using hybrid Beck model (B3LYP), ESP showed regular distribution of charge density of whole molecule when one of the two proton is removed from a-carbon, the ESP for HOMO electron density is heavily localized on a negative carbon, reflect the reactivity of thiobarbituric molecule and show it as highly effective nucleophile when act into nucleophilic substitution reactions.